Aviation Induced Cirrus in Observations and Models - Schumann, Ulrich (2010)
Cirrus clouds cause a warming of the Earth during night and possibly a cooling during day time. Under suitable atmospheric conditions, aircraft induced contrails contribute to the formation or change of cirrus clouds. The amount of this effect has been under discussion for quite some time. So far, contrails have been estimated to contribute a few percent to global climate change, but this contribution is expected to grow unless suitable mitigation options are taken into account. We recently made considerable progress by analyzing satellite and in-situ data showing contributions of aviation induced contrail cirrus together with new model developments. This talk will present major findings and list open questions. Some of the results are of relevance also for understanding cirrus properties in general. In particular the seminar will address Satellite observations of the diurnal cycle of cirrus cover in the North Atlantic Region in correlation with traffic data. The data show a unique fingerprint dominated by two correlated maxima of traffic and cirrus cover due to rush-hours with west-bound or eastbound air traffic. In order to explain the observed correlations, a new “Contrail Cirrus Prediction Tool” (CoCiP) has been developed to simulate contrail cirrus resulting from a single flight as well as from a fleet of cruising aircraft, flight by flight, regionally or globally. The method predicts contrail cirrus for given air traffic and weather prediction data. The radiative forcing by contrail cirrus is estimated as a function of cover, optical depth and effective radius of the cirrus particles. For estimate of the effective radius a new concept is introduced which is calibrated by in-situ cirrus measurements. Finally we present an outlook to the ML-CIRRUS project with the new research aircraft HALO.